If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(5+3)=2(9x+3)
We move all terms to the left:
4(5+3)-(2(9x+3))=0
We add all the numbers together, and all the variables
-(2(9x+3))+48=0
We calculate terms in parentheses: -(2(9x+3)), so:We get rid of parentheses
2(9x+3)
We multiply parentheses
18x+6
Back to the equation:
-(18x+6)
-18x-6+48=0
We add all the numbers together, and all the variables
-18x+42=0
We move all terms containing x to the left, all other terms to the right
-18x=-42
x=-42/-18
x=2+1/3
| 7x+677x+67+8(8xx-2)=7x−677x−67. | | 6t-3=7t-8= | | 2c-2=4c-6=0.4 | | –3/4m=21 | | 10=5+6x | | 30=5+6x | | 45=5+6x | | 40=5+6x | | 0.10x+0.03(38500-x)=2590 | | 50=5+6x | | 100=5+6x | | –130=g–19 | | 5x-3=7+5 | | g–(–40)=–184 | | 100=-15+6x | | 100=-2+7x | | 10=-2+7x | | –4+y=12 | | 20=-2+7x | | 30=-2+7x | | 10=-15+6x | | 20=-15+6x | | 30=-15+6x | | 50=-15+6x | | 5w=6w-14 | | 45=-2+7x | | 45=-15+6x | | 7x-11-12x-4=-5 | | 40=-15+6x | | 5(x-4)+40=-20 | | 5(x+4)+40=-20 | | 50=-2+7x |